Pelatihan dan Pendampingan untuk Meningkatkan Minat Wirausaha Mahasiswa - Gadis Arniyati Athar; Bantali, Ampun; Abdi Samra Caniago; Olivia, Hastuti (JPM: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service activity is to increase interest in entrepreneurship in the Islamic Religious Education Study Program of STAI Syekh H. Abdul Halim Hasan Al Ishlahiyah Binjai TA 2020/2021. The method used is the entrepreneurship program development method from Ndou and the entrepreneurship learning method from Esmi, which has 4 stages and methods as follows; 1) Phase of Inspiration (Inspiration); activities in this phase are entrepreneurship seminars. 2) Engagement Phase; activities in this phase of business practice. 4) Sustainability; Investment project, but this stage was not implemented due to time constraints. Overall this Community Service activity was carried out well. The team provides recommendations for the sustainability of student entrepreneurship namely; 1) Universities must build a Center for Study and Development of Student Entrepreneurship Activities, 2). Universities must provide facilities for student campus entrepreneurship activities, 3) Universities must provide activities that generate motivation and interest in student entrepreneurship, 4) Socialise the Merdeka Learning Campus Merdeka program which facilitates entrepreneurial activities, namely Wirausaha-Merdeka so that students can be interested to become an entrepreneur.